2020
DOI: 10.3389/fphar.2020.540479
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Attenuates Renal Ischemia/Reperfusion Injury by a PI3K/Akt/Bad-Mediated Anti-apoptosis Signaling

Abstract: Ischemic/reperfusion (I/R) injury is the primary cause of acute kidney injury (AKI). Gastrin, a gastrointestinal hormone, is involved in the regulation of kidney function of sodium excretion. However, whether gastrin has an effect on kidney I/R injury is unknown. Here we show that cholecystokinin B receptor (CCKBR), the gastrin receptor, was significantly up-regulated in I/R-injured mouse kidneys. While pre-administration of gastrin ameliorated I/R-induced renal pathological damage, as reflected by the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 55 publications
3
51
0
Order By: Relevance
“…The PI3K/Akt-signaling pathway has been shown to play a vital role in survival signals in several neuronal cell types [ 19 , 64 , 65 ]. The function of Akt on cell survival signals has been linked to inhibiting the cytoplasmic cell death machinery and regulating the expression of genes involved in cell death and survival [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/Akt-signaling pathway has been shown to play a vital role in survival signals in several neuronal cell types [ 19 , 64 , 65 ]. The function of Akt on cell survival signals has been linked to inhibiting the cytoplasmic cell death machinery and regulating the expression of genes involved in cell death and survival [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt-signaling pathway has been shown to play a vital role in survival signals in several neuronal cell types [ 19 , 64 , 65 ]. The function of Akt on cell survival signals has been linked to inhibiting the cytoplasmic cell death machinery and regulating the expression of genes involved in cell death and survival [ 64 , 65 ]. The PI3K/Akt-signaling pathway involved in the protective role against Aβ toxicity has been found associated with many natural compounds and antioxidant reagents, such as salidroside [ 66 ] and nitroso glutathione [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CsA‐evoked ROS production and diminished antioxidant defenses result in lowered mitochondrial membrane potential, increased mitochondrial pore permeability, and consequent release of the pro‐apoptotic cytochrome c to the intermembrane space, thereby, triggering the apoptotic machinery. In the context of apoptosis, phosphoinositide‐3‐kinase (PI3K)/protein kinase B (AKT) pathway has been characterized as a prosurvival pathway that orchestrates cellular growth and survival (Liu et al., 2020). Notably, interventions that can activate the PI3K/AKT signaling have been reported to effectively dampen the apoptotic events and renal injury in several renal pathologies (Arab et al, 2018a,b; Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of apoptosis, phosphoinositide‐3‐kinase (PI3K)/protein kinase B (AKT) pathway has been characterized as a prosurvival pathway that orchestrates cellular growth and survival (Liu et al., 2020). Notably, interventions that can activate the PI3K/AKT signaling have been reported to effectively dampen the apoptotic events and renal injury in several renal pathologies (Arab et al, 2018a,b; Liu et al., 2020). The PI3K/AKT pathway has been reported to counteract endothelial cell apoptosis via upregulation of endothelial nitric oxide synthase (eNOS) that generates the vasodilator nitric oxide (Hasan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, nobiletin inhibited inflammatory cytokines and regulated inducible nitric oxide synthase (iNOS)–endothelial nitric oxide synthase (eNOS) expression, thereby protecting rats from renal IRI ( 8 ). Gastrin attenuated renal IRI by anti-apoptosis ( 9 ). Congruously, our previous results have indicated that anti-oxidative stress could alleviate renal IRI.…”
Section: Introductionmentioning
confidence: 99%